Analysis of the dynamics of interaction between profitability and liquidity using a predator-prey model approach - Jamal, Sri Wahyuni; Suparno, Suparno; Fauziah, Fenty; Rashid, Umi Kartini; Latief, Azhar (Universitas Negeri Surabaya, Indonesia, 2024)
Profitability and liquidity are among the critical issues that must be studied and considered by the management of every organisation as their foremost task. This research aims to analyse the bidirectional dynamics of profitability ratios and liquidity ratios over time. This research also aims to present forecasted values of profitability and liquidity for the next five years. The data used in this study are obtained from the food industry company’s annual reports for the period 2011-2022. This research adopts a predator-prey model containing a pair of non-linear differential equations to describe the interaction between two species. The results show that the predator-prey model can explain the bidirectional dynamics of profitability ratios and liquidity ratios with high accuracy. Besides, this study indicates that the type of relationship between profitability and liquidity is predator-prey. The forecasting results show that for 2023-2027, both profitability and liquidity tend to decrease. Based on the data, the company’s profitability and liquidity dynamics periodically fluctuate over time. This fluctuation indicates a positive sign for company’s profitability and liquidity are in good condition. In the future, company has to take preventive measures to continue stabilising its profitability and liquidity.